Mr. Reid Holmes, Hospital Administrator - (:unkn) unknown (Coy C. Carpenter Library, 2008)
Description source: Egbert Davis, Jr. Oral History transcript 1/19/1979.
Reid Holmes, North Carolina Baptist Hospital Administrator from 1945-1970, was important to the development of the Medical Center. Holmes was a remarkable individual and well prepared for the administration of a hospital. He was diplomatic in dealing with the higher administration staff. He was smooth and persuasive in getting his points across, but was also a well-respected individual in the community.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth